The Role of Teacher Attitudes in Shaping Students' Academic Confidence: A Survey-Based Study - Nargus Zafar; Asma Akram Butt; Dr.Rukhsana Sardar (Journal of Religion and Society, 2025)
This quantitative, survey-based study investigated the relationship between secondary school students’ perceptions of teacher attitudes and their academic confidence. Grounded in Social Cognitive Theory (Bandura, 1997) and Self-Determination Theory (Deci & Ryan, 1985), the research sought to examine (1) whether a significant relationship exists between perceived teacher attitudes and students’ academic confidence, and (2) how positive teacher attitudes influence students’ confidence levels. A stratified random sample of 300 secondary school students (Grades 9 and 10) from public and private schools in Narowal, Pakistan, participated in the study. Data were collected using two standardized instruments: the Teacher Attitudes Inventory and the Academic Confidence Scale, both of which demonstrated strong internal reliability (α = .88 and .85, respectively). Statistical analysis using SPSS Version 26 included descriptive statistics, Pearson’s correlation, and linear regression. The results revealed a significant positive correlation (r = 0.64, p < .001) between perceived teacher attitudes and students' academic confidence. Regression analysis indicated that teacher attitudes significantly predicted academic confidence (B = 0.70, R² = 0.41, p < .001), explaining 41% of the variance in the outcome variable. The findings affirm that positive teacher attitudes such as support, respect, fairness, and enthusiasm are critical psychological resources that foster students’ belief in their academic abilities. The study highlights the importance of incorporating emotional intelligence, reflective practice, and student feedback into teacher training and professional development programs. Limitations include the use of cross-sectional data and reliance on student self-reports. Future research is recommended to adopt longitudinal and mixed-method approaches. Overall, the study reinforces the need to prioritize positive teacher-student interactions as a strategic tool to enhance student confidence and academic performance in secondary education. Keywords: Teacher Attitudes, Shaping Students, Academic Confidence, A Survey-Based Study